The structure of hydropyle cells in dormant eggs of the South African brown locust, Locustana pardalina (Walk.) - Saacks, Sharon (My University, 2008)
Water regulation in drought-resistant eggs of the brown locust Locustana pardalina (Walk.) may be mediated by specialised serosal cells in the hydropyle region. These cells are thought to both supply water to the embryo and to waterproof the egg during very dry periods. The characteristics of hydropyle cells in quiescent eggs were examined at intervals during desiccation at 15-22% RH, and again after rehydration. Embryos were pre-catatreptic and any pre-existing diapause condition had terminated. Egg water contents and the sizes of cells and nuclei decrease with desiccation, and increase after rehydration. Deformable cell and nuclear membranes accommodate size changes. Surface microvilli increase in length with rehydration and cytoplasmic vacuoles become larger, indicating absorption of water. Organelle integrity improves upon rehydration while autophagy remains common. Evidence of the production and secretion of a waterproofing protein substance, while expected, was not found. However, electron dense vesicles present at the apical boundaries suggest that the cells may nonetheless produce some substance in that region. Dehydrated and rehydrated cells show signs of desiccation damage, but this does not affect cell functioning as embryos from rehydrated eggs developed to hatching. The results indicate that, in addition to structural protection, hydropyle cells may have molecular protection against desiccation damage, and may be able to undertake limited repair upon rehydration.
Keywords: Locusts; South Africa